The image of Emperor Alexander I in the epic novel by L.N. Tolstoy “War and Peace” - Valeria G. Andreeva (Studia Litterarum)
The article analyzes the image of Emperor Alexander I presented by Leo Tolstoy in his epic novel “War and Peace,” and states that the writer did not aim to create the most believable portrait of the sovereign. He showed the person who stood at the head of a great country during the years of the liberation war. The author of the work proves that the heroes of the epic, including historical figures, are assessed by the writer not from the position of their determinism by society and the era, but exclusively from the position of eternity and life’s truth. The peculiarity of the artistic world of the work is that the image of Alexander I turns out to be included in the huge design of the artistic universe, representing the author’s historiosophical thought. The article notes that in the image of the emperor Tolstoy deliberately emphasized the weaknesses and contradictions of a person who was mistaken because of the multidirectional influences exerted on him. The voices of the heroes in certain scenes are analyzed, episodes that have a paired character and are indicators of the precedent picture of the world characteristic of the epic are noted. In the artistic world of the work, the writer illustrates the deep connection between the tsar and the Orthodox people. The image of the sovereign is associated for each of the Russian people with the thought of the highest truth, intercession, however, the deep meanings lead the reader to the discovery of the only fair judgment — the Divine. The writer condemns the senseless worship of the emperor, but affirms a high spirit of service to the emperor as God’s anointed one.